2019
DOI: 10.1016/j.bbmt.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Family Psychosocial Risk in Pediatric Hematopoietic Stem Cell Transplantation with the Psychosocial Assessment Tool

Abstract: Family psychosocial risk screening is an important initial step in delivering evidence-based care in hematopoietic stem cell transplantation (HCT). Establishing an evidence-based screening approach that is acceptable, reliable, and valid is an essential step in psychosocial care delivery. This is a 3-institution multimethod study. In part 1, caregivers of children about to undergo HCT (n = 140) completed the Psychosocial Assessment ToolÀHematopoietic Cell Transplantation (PAT-HCT), a brief parent report screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
(64 reference statements)
1
27
0
2
Order By: Relevance
“…It began with a presentation on psychosocial care delivery (AK) describing the type of clinicians providing psychosocial care and its structure (e.g., integrated vs consultation models). Participants also learned about the purpose and results of the prior studies and the four themes were presented. All questions posed to the group were open‐ended.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It began with a presentation on psychosocial care delivery (AK) describing the type of clinicians providing psychosocial care and its structure (e.g., integrated vs consultation models). Participants also learned about the purpose and results of the prior studies and the four themes were presented. All questions posed to the group were open‐ended.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, psychosocial care in HCT is not driven by clearly articulated or tested models nor are evaluations and subsequent treatment approaches regularly used . In this paper, we propose a psychosocial clinical care pathway (PCCP) that is informed by and derived from our mixed methods research with HCT caregivers and providers . The PCCP is a multidisciplinary approach that standardizes services provided for a group of patients with a sequence of well‐defined steps.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8,9, 11, 29,17 ,16, 29 We showed that PAT can be completed at diagnosis 17 and it has been shown to impact psychosocial outcomes for mothers at higher levels of distress when results are shared with staff. 30 Our group has adapted the PAT for use in hematopoietic stem cell transplantation (HCST) 31 including development of a clinical pathway, guided by stakeholder input, that could facilitate its integration in clinical care. 32,33 We have also adapted the PAT for use in Sickle Cell Disease, adding items to capture relevant aspects of the social context for families (e.g., school absences, changes in housing).…”
Section: Introductionmentioning
confidence: 99%